Karakterisasi Isoterm Adsorpsi Fe dan Mn Pada Sampel Air Asam Tambang - Mycelia Paradise (ReTII, 2023)
This study aimed to analyze the adsorption pattern of heavy metals. Adsorption tests were conducted on Fe and Mn in Acid Mine Drainage (AAT) samples containing Fe 13.006 mg/L and Mn 30.590 mg/L at various time and adsorbent mass variations. The experimental results showed that the composite mass of 5 grams could reduce the iron concentration to 99.35%, but the adsorbent mass of 2.5 grams is more efficient because it succeeded in reducing the iron concentration to 0.1484 mg/L within 30 minutes, thus meeting the quality standards set. The adsorption pattern in this study is described through the adsorption isotherm curve which has a correlation coefficient (R2) close to 1. Based on the analysis results, Fe adsorption followed the Langmuir isotherm pattern with R2 = 0.998, while Mn adsorption followed the Langmuir isotherm pattern with R2 = 0.997. The analysis showed that the correlation coefficient in Langmuir isotherm was higher than Freundlich isotherm for both Fe and Mn, indicating a very strong level of correlation in the Langmuir model. The adsorption mechanism observed in this study is characterized as chemical adsorption. The adsorbent exhibits an adsorption capacity of 1.286 mg/g for Fe and 1.031 mg/g for Mn under the optimal conditions of a 2.5-gram mass of adsorbent for 30 minutes.